2021
DOI: 10.21037/qims-20-1203
|View full text |Cite
|
Sign up to set email alerts
|

A new nomogram for predicting the malignant diagnosis of Breast Imaging Reporting and Data System (BI-RADS) ultrasonography category 4A lesions in women with dense breast tissue in the diagnostic setting

Abstract: Background: Biopsy has been recommended for Breast Imaging Reporting and Data System (BI-RADS) category 4 lesions. However, the malignancy rate of category 4A lesions is very low (2-10%). Therefore, most biopsies of category 4A lesions are benign, and the results will generally cause additional health care costs and patient anxiety. Methods: A prediction model was developed based on an analysis of 418 BI-RADS ultrasonography (US) category 4A patients at Sun Yat-sen Memorial Hospital. Univariate and multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
0
26
2
Order By: Relevance
“…Some of the nomograms were based on subjective evaluations using qualitative descriptors (e.g., spiculated, rounded, microcalcification, etc. ), which are highly dependent on the level of expertise and experience and can suffer from a large intra- and inter-observer variability ( 36 39 ). However, other nomograms were based on quantitative methods such as radiomics, which can objectively describe tumor phenotypes using numerical features extracted from radiological images ( 14 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the nomograms were based on subjective evaluations using qualitative descriptors (e.g., spiculated, rounded, microcalcification, etc. ), which are highly dependent on the level of expertise and experience and can suffer from a large intra- and inter-observer variability ( 36 39 ). However, other nomograms were based on quantitative methods such as radiomics, which can objectively describe tumor phenotypes using numerical features extracted from radiological images ( 14 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al found no significant difference between homogenous and heterogeneous echo patterns in malignant lesions. 31 Thus, we believe that eliminating “heterogeneous” echo patterns and adding “internal echogenic homogeneity of solid mass” to the BI-RADS lexicon would make for a good new descriptor of heterogeneous masses that would let observers describe masses more reproducibly.…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms, which are easy-to-use graphical predictive tools, have been widely applied to predict numerous binary and prognostic outcomes ( 15 ). In previous studies, nomograms have provided detailed probabilities of different clinical events and helped clinicians make decisions in the management of breast cancer ( 16 , 17 ). However, there seems to be no nomogram based on MRI features for the prediction of TNBC-MC and TNBC-NMC in the literature.…”
Section: Introductionmentioning
confidence: 99%